Nivel de conocimiento en manejo de residuos sólidos hospitalarios y actitudes hacia la conservación ambiental en el personal del IPRESS Centro de Salud Militar Divisionario Santa Rosa Iquitos 2024 - Peñaloza Bacigalupo, Carlos Dante (2025)
In the present research work, the general research question was what is the association between knowledge in hospital solid waste management and the attitude towards environmental conservation in the administrative and professional staff of the IPRESS Military Health Center Santa Rosa Division. 2024, so the general objective was to determine the relationship or association between the level of knowledge in hospital solid waste management and the attitude towards environmental conservation in the workers of the IPRESS Military Health Center Santa Rosa Division. Iquitos. 2024. It was quantitative, simple relational and non-experimental design. The target population of the study was 67 workers, but the sample was 59 workers, inclusion and exclusion criteria were considered, the technique was the survey and the instrument were two questionnaires of twenty and fifteen items each, the same ones that passed the validity tests through the Aiken Validity index and reliability with the two-halves test with the Pearson r statistic. The data were analyzed, processed, and tabulated using the statistical software R base and studio version 4.4.1, as well as Python version 3.11.4. The results indicate that, while workers have some positive aspects, such as knowledge about waste classification, there is an urgent need to improve training in critical areas such as transportation, collection, and storage of waste, as well as the proper use of personal protective equipment. Likewise, it was evident that younger workers have better knowledge about the management of hospital solid waste, while those over 60 years of age have average levels of knowledge. Furthermore, the work area also significantly influences knowledge, with workers in the healthcare area showing better results than those in the administrative area. Likewise, there are differences observed in attitudes towards environmental conservation according to age and work area, since younger workers and employees in the administrative area show a predominantly favorable attitude towards environmental conservation, while workers in healthcare areas and older workers present somewhat less marked attitudes. The results of the statistical tests (Chi Square and Gamma) show a weak and non-significant association between the level of knowledge in hospital solid waste management and the attitude towards environmental conservation in the workers of the Santa Rosa Divisional Military Health Center in Iquitos.